Pengembangan Sistem Pencatatan dan Pelaporan Surveilans Demam Berdarah Dengue di Dinas Kesehatan Kota Tasikmalaya Tahun 2021 - Irinedian Sribudaya; Arief Hargono; Lucia Yovita Hendrati; Gian Sugianto (Media Gizi Kesmas, 2023)
Background: The city of Tasikmalaya experienced a significant increase in cases of Dengue in 2020. This was evidenced by the incidence rate of Dengue, which was 229 per 100,000 people, and the Dengue mortality rate of 1.42%. The implementation of Dengue surveillance in the Tasikmalaya City Health Office faced delays in reporting suspects, cases, and Larva-free rates. Tasikmalaya City Health Office needs a surveillance system that can detect cases early to ensure timely reporting. Objectives The aim of this study is to design the development of a recording and reporting system for Dengue surveillance in the Tasikmalaya City Health Office. Methods: This study employed a qualitative research design with an action research approach for system development. Primary data were collected through in-depth interviews with officers and manager of Dengue surveillance. Secondary data were obtained through document studies on the surveillance forms used. The data analysis was conducted descriptively. The development design of the Dengue surveillance system was created using a Data Flow Diagram. Results: The types of information needed for the development of Dengue surveillance include the number of suspects, cases, and deaths from Dengue Fever on a weekly basis based on person, place, and time; trends in suspects, cases, and deaths from Dengue on a weekly basis; as well as the monthly Larva-free rates. The required data consist of suspect/case data and Dengue death data from weekly reports by primary health centers; a recapitulation of the number of suspects, cases, and Dengue deaths; Larva-free rates; and the population reported monthly by the primary health centers. Conclusions: The Tasikmalaya City Health Office aims to improve Dengue surveillance by implementing weekly data processing and analysis activities, weekly reports from primary health centers, and biweekly meetings. This will improve workflow procedures and monitor the increase in Dengue cases.